Sosialisasi English For Bussiness Peningkatan Branding Produk Umkm bagi Pelaku Usaha di Desa Sukamulya (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
English for Business: Strategies for Enhancing MSME Product Branding.The English for Business program, focusing on strategies for enhancing MSME product branding, is designed to help micro, small, and medium-sized enterprise (MSME) owners understand the importance of using English to build a strong product image, develop attractive promotional materials, and communicate professionally with prospective business partners. This community service program aims to provide practical knowledge on the application of English in business contexts, particularly in product branding, digital marketing, and cross-cultural communication. By improving English literacy among MSME entrepreneurs, the program is expected to enhance the competitiveness of local products in the global market. Branding is a crucial aspect for MSMEs in establishing and expanding their businesses, as it increases product attractiveness, strengthens business identity, and contributes to higher sales performance. As a result of the community outreach and socialization program on improving product branding for MSME entrepreneurs in Sukamulya Village, one business with significant growth potential was identified, namely Bu Ana's Chips (Keripik Bu Ana). Prior to the program, many MSMEs in Sukamulya Village had been operating and producing goods for years but had not yet been officially registered. Following field surveys and assistance provided during the program, ten MSMEs were successfully registered and obtained their Business Identification Number (NIB) through the East Ogan Komering Ulu (OKU Timur) Regency Cooperative Office.